Interaction between memory impairment and depressive symptoms can exacerbate anosognosia: a comparison of Alzheimer's disease with mild cognitive impairment. (4th May 2019) - Oba, Hikaru; Matsuoka, Teruyuki; Imai, Ayu; Fujimoto, Hiroshi; Kato, Yuka; Shibata, Keisuke; Nakamura, Kaeko; Narumoto, Jin
ABSTRACT: Objective: To investigate the effects of interactions between memory impairment, depressive symptoms, and anosognosia. Methods: Anosognosia for memory impairment was assessed in 118 patients with Alzheimer's disease (AD), 47 patients with mild cognitive impairment (MCI), and 17 non-diagnosed controls (NC) using a questionnaire and evaluation of the anosognosia score as the discrepancy between ratings of the patient and a relative. Demographic characteristics, such as the relationship of the patient with the relative and the activities of daily living (ADL) were evaluated. Memory impairment was evaluated with the Rivermead Behavioral Memory Test (RBMT), depressive symptoms were evaluated using the Geriatric Depression Scale (GDS) 15 items version. Results: In the MCI group, a stepwise multiple regression analysis showed an interaction between RBMT and GDS scores, and simple slope analysis indicated that scores for RBMT at low GDS (-1 standard deviation) were positively correlated with self-rated memory impairment. In the AD group, the relationship of the patient with the relative, ADL, and GDS and RBMT scores were associated with the anosognosia score. Conclusion: Patients with MCI who have no depressive symptoms may be able to more accurately evaluate their memory impairment than those who have depressive symptoms and patients with AD. The evaluation by relatives, depressive symptoms or ADL of patients may distort evaluation of anosognosia for memory impairment in patients with AD or MCI. It seems necessary to include not only depression scale scores but also results of objective memory tests in the patients' medical information for the correct assessment of anosognosia.